1994
DOI: 10.1093/infdis/170.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Activation by Helicobacter pylori Lipopolysaccharides

Abstract: Helicobacter pylori-induced release of toxic substances by neutrophils could be of potential importance in the pathogenesis of gastroduodenal inflammatory diseases. Lipopolysaccharide (LPS) has the ability to induce neutrophil activation at very low concentrations. Neutrophil oxidative metabolism and enzyme release were assessed after stimulation of neutrophils with various preparations of LPS from H. pylori and compared with that obtained with Salmonella typhimurium LPS. No direct activation of neutrophils by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 36 publications
4
59
1
Order By: Relevance
“…Gram-negative rods contain lipopolysaccharide (LPS). LPS is a well-known virulence factor which promotes infection by interference with the host immune response (12) and can activate neutrophils (12,23,27). Although the reason why growth of the microflora in the small intestine was changed by the BFMeT treatment is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Gram-negative rods contain lipopolysaccharide (LPS). LPS is a well-known virulence factor which promotes infection by interference with the host immune response (12) and can activate neutrophils (12,23,27). Although the reason why growth of the microflora in the small intestine was changed by the BFMeT treatment is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Expression profiling analysis of the B. contaminans bceF::Tp mutant indicated an upregulation of the lpxO gene, which encodes a putative dioxygenase required for acyl chain hydroxylation (7), suggesting that different degrees of 2-hydroxylation might be present with bceF::Tp mutant and wild-type strains. Modified lipid A structures with different phosphorylation or acylation patterns elicit different host immune responses (65,66). Nevertheless, Palfreyman and coauthors showed that B. cepacia complex cell-free supernatants can also increase IL-8 production, suggesting that other factors besides LPS can enhance the immune response (67).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that ROS was probably induced (in at least some neutrophil populations) by LPS or cytokines in the circulation as a result of preinoculation with 1326/28⌜ r . Stimulation of human neutrophil ROS has previously been shown to occur in response to LPS (27,43), particularly rough forms (33), and the stimulatory effect of gamma interferon on neutrophil gp91-induced ROS has been widely studied with respect to chronic granulomatous disease (12,32,34). TNF-␣ production in response to Staphylococcus aureus also stimulates neutrophil ROS, although the ROS pathway in the latter case appears to involve myeloperoxidase rather than NADPH phox (24).…”
Section: Discussionmentioning
confidence: 99%